2009
DOI: 10.1002/gps.2354
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to atypical antipsychotics (risperidone or olanzapine) in older patients with schizophrenia: an open study of 3½ years duration

Abstract: Overall adherence with atypical medication was good with almost two-thirds of the patients remaining on their randomisation drug for the interval in which they were under observation. Patients taken off depot were less likely to be adherent but there was no significant difference in adherence between olanzapine and risperidone. Scrutiny of the survival curves suggested that non-adherence is an early event in treatment and patients adherent at 6 months were likely to remain adherent over a longer time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
10
1
1
Order By: Relevance
“…Altogether, we included 63 reports (59 randomized studies) with 45,787 participants (median: 255 participants/study, range: from 12 to 18,154) (Table ). The mean age of the population was 37.6±7.0 years; 62.1±13.3% were male and 61.1±28.8% were white.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, we included 63 reports (59 randomized studies) with 45,787 participants (median: 255 participants/study, range: from 12 to 18,154) (Table ). The mean age of the population was 37.6±7.0 years; 62.1±13.3% were male and 61.1±28.8% were white.…”
Section: Resultsmentioning
confidence: 99%
“…20 Other studies had also found similar results. [21][22][23][24] However Eticha T et al had observed higher prevalence of treatment adherence in younger schizophrenic patients 25 which can be explained by Dolder CR et al according to whom age had no significant effect on treatment adherence. 26 In the present study 68.4% males and only 59.6% females were non adherent to medications.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…1,19 For instance, both olanzapine and clozapine may have slightly higher adherence rates compared to risperidone. 20 The complexity of the treatment regimen is also important for adherence; data have shown that number of doses per day is inversely related to adherence. 21,22 More complex regimens may disrupt a patient's daily routine and further compound problems with adherence that are due to memory deficits.…”
Section: Treatment Regimenmentioning
confidence: 99%